2014
DOI: 10.1080/13854046.2014.950335
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilesional Bias and Processing Speed are Important Predictors of Functional Dependency in the Neglect Phenomenon After a Right Hemisphere Stroke

Abstract: Visuospatial neglect (VSN) predicts unfavorable functional outcome in stroke patients. This study examined the relative importance of different core symptoms of VSN as predictors of functional dependency. A consecutive series of 105 right hemisphere stroke patients were tested early after stroke on three basic symptoms of VSN (omissions, asymmetry of omissions and ipsilesional bias of attention) and on two symptoms related to VSN (processing speed and repetitive target detections in visual search). Neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 65 publications
(89 reference statements)
2
8
0
Order By: Relevance
“…Altogether, these results are in line with previous studies that have associated slow processing speed with RH lesions in general (Farne et al, 2004;Heilman et al, 1993) and even more so with visual neglect (Erez et al, 2009;Bonato, 2012;Gerritsen et al, 2003). In addition, our results support the previous findings that slow processing speed is a rather persistent residual symptom of neglect and may be seen in patients with clinically recovered neglect for several months (Harvey & Gilchrist, 2002;Samuelsson et al, 1998;Viken, 2014), or as in our study, even a year after stroke. There is hardly any previous research regarding processing speed and its recovery specifically in a subgroup of RH patients with initially milder inattention symptoms after stroke but no actual neglect (i.e.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Altogether, these results are in line with previous studies that have associated slow processing speed with RH lesions in general (Farne et al, 2004;Heilman et al, 1993) and even more so with visual neglect (Erez et al, 2009;Bonato, 2012;Gerritsen et al, 2003). In addition, our results support the previous findings that slow processing speed is a rather persistent residual symptom of neglect and may be seen in patients with clinically recovered neglect for several months (Harvey & Gilchrist, 2002;Samuelsson et al, 1998;Viken, 2014), or as in our study, even a year after stroke. There is hardly any previous research regarding processing speed and its recovery specifically in a subgroup of RH patients with initially milder inattention symptoms after stroke but no actual neglect (i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Initial ipsilateral orienting bias, on the other hand, is often present for 6 to 7 (Bonato, 2012; Kettunen et al, 2012; Samuelsson et al, 1996), even 12 months (Mattingley et al, 1994) after stroke, despite the recovered ability to reorient attention toward the contralesional side. Similarly, slow processing speed has been seen as a residual symptom in clinically recovered neglect patients for 3 to 7 months post-stroke (Harvey & Gilchrist, 2002; Samuelsson et al, 1998; Viken, 2013). It has also been shown that even if patients no longer show neglect symptoms in simpler tasks, attentionally more demanding situations, as often encountered in daily activities, may still provoke residual symptoms, such as ipsilateral orienting bias (Friedrich & Margolin, 1993; Taylor, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether and how it is possible to isolate an advantage in ipsilesional processing without re-referencing performance to the contralesional side of space remains an open issue. Ipsilesional biases have been described as being predictive of long-term deficits, altogether with unspecific slowing (Viken et al, 2014). The clinical value of these findings perfectly summarizes the possibility that, also within a context of lateralized deficits, performance can be heavily affected by unspecific impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies have reported impact on outcome at the end of rehabilitation, but several have reported impact at up to 1 or even 2 years post-stroke. 24,26,28,31,32,35 Therefore, participants with right hemisphere large vessel distribution infarcts might be expected, on average, to demonstrate less gain with treatment than participants with left hemisphere cortical lesions.H3B. Furthermore, because walking was not part of the home-based LEAPS therapy, it might be anticipated that recipients of this therapy would show lesser gains in walking speed because they were presumably left on their own to a greater extent in any walking they did.…”
mentioning
confidence: 99%